(untitled) (TSUL LEGAL REPORT, 2026)
This article provides an in-depth analysis of the development of anti-corruption policies in Uzbekistan. A significant shift occurred under President Shavkat Mirziyoyev’s leadership, with the introduction of comprehensive reforms. These included the establishment of a dedicated Anti-Corruption Agency and numerous presidential decrees aimed at preventing corruption risks, enhancing public oversight, and ensuring merit-based public service appointments. In this context, the 2022 Development Strategy reinforced a strict zero-tolerance policy toward corruption, emphasizing institutional accountability. However, significant obstacles continue to impede progress to some extent. Over a four-year period, more than 9,500 corruption offenses were recorded, causing substantial financial damage. Corruption remains entrenched due to legislative gaps and inadequate enforcement. Furthermore, the author concludes that corruption should be understood as a deeply rooted socio-economic and ethical challenge. To prevent and eradicate corruption, integrated reforms, rigorous oversight, risk assessment, civic engagement, and adherence to ethical standards are essential.